2012
DOI: 10.25249/0375-7536.2012424744753
|View full text |Cite
|
Sign up to set email alerts
|

Morphological and petrographic patterns of the pahoehoe and ´a´ā flows of the Serra Geral Formation in the Torres Syncline (Rio Grande do Sul state, Brazil)

Abstract: The Serra Geral Formation volcanic sequence in Torres Syncline (Rio Grande do Sul state, Brazil) may be divided into main valley, intermediate zone, and southern hinge. The first volcanic episode along the syncline is characterized by low eruption rates (< 5 m 3 /s) forming compound pahoehoe flows near the dunes and ponded ones in interdune areas. The second episode is constituted by simple flows that rarely exceed 3 m in thickness, erupted with similar eruption rates. The third is defined by ´a´ā flows that a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 26 publications
(28 reference statements)
0
5
0
Order By: Relevance
“…Previous studies in the Paran a CBP have described the simple flows from Unit II as 0 a 0 a lava flows (Hartmann et al, 2010;Lima et al, 2012;Waichel et al, 2012). However, we identified a fourpart structure characterized by an autobreccia top, a coherent vesicular upper crust, a dense core and a lower vesicular crust similar to the rubbly pahoehoe flows defined by Keszthelyi (2000.…”
Section: Emplacement Of Lava Flows In Southern Paran A-etendekamentioning
confidence: 65%
See 1 more Smart Citation
“…Previous studies in the Paran a CBP have described the simple flows from Unit II as 0 a 0 a lava flows (Hartmann et al, 2010;Lima et al, 2012;Waichel et al, 2012). However, we identified a fourpart structure characterized by an autobreccia top, a coherent vesicular upper crust, a dense core and a lower vesicular crust similar to the rubbly pahoehoe flows defined by Keszthelyi (2000.…”
Section: Emplacement Of Lava Flows In Southern Paran A-etendekamentioning
confidence: 65%
“…Locally high-TiO 2 lavas (Ubirici type) occur in the south and are contemporaneous with the Gramado type (Peate et al, 1999). Waichel et al (2006) described pahoehoe flows in the central portion of Parana CBP and recent works Lima et al, 2012) have also identified pahoehoe and 0 a 0 a lava flows in the southern portions of the province in the Torres Syncline area.…”
Section: Geological Setting Of Torres Synclinementioning
confidence: 94%
“…The region known as "Aparados da Serra" in southern Brazil consists of the silicic volcanic rocks of the Serra Geral Group, which is linked to the PEMP. These silicic rocks are related to tabular deposits of great extension, whose origin is still a subject of discussion, and the debate regarding its genesis by lava flows (Bellieni et al 1988, Comin-Chiaramonti 1988, Henry & Wolff 1992, Umann et al 2001, Lima et al 2012b, Polo et al 2017a, b, Guimarães et al 2018, Lima 2018, Simões 2018 or pyroclastic flows (Petrini et al 1989, Roisenberg 1989, Whittingham 1989, Milner et al 1992, Luchetti et al 2018 remains. In the investigation of the Serra Geral volcanism, the emphasis is usually given to the lithochemical and isotopic aspects, usually organizing the data on a regional scale, where aspects related to local structures, flow regime and effusion are suppressed or overlooked (Waichel 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Pumice, fiamme, crystalloclasts, and lithoclasts were not observed, and a vitrophyre under scanning electron microscopy indicated a compact holohyaline condition, with crystallites and microliths of feldspars randomly distributed, typical of silicic flows. Lima et al (2012bLima et al ( , 2018 identified feeder systems related to the silicic lavas and, according to these authors, the presence of a feeder root suggests that, in certain portions, the structures may assume dome shapes in response to the resistance to the flow. Polo (2014) concludes that the silicic volcanic sequences of the Soledade region are widely dominated by effusive deposits and that the extrusion occurred through fissures.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation